2015
DOI: 10.5901/mjss.2015.v6n6s5p257
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development of a Foreign-Language Tertiary Teacher: Competence-Based Approach

Abstract: The article describes research aimed at outlining the pathways to structure EFL tertiary teachers ' professional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…At some institutions of higher education, the problem is solved with in-service teacher training (Krupchenko, Inozemtzeva and Prilipko 2015). Considering it a good way out, we also support the idea of pre-service teacher training at tertiary level which is to be based on the formed competences of an EFL school teacher and a practitioner of EFL for English major undergraduates.…”
Section: Introductionmentioning
confidence: 67%
“…At some institutions of higher education, the problem is solved with in-service teacher training (Krupchenko, Inozemtzeva and Prilipko 2015). Considering it a good way out, we also support the idea of pre-service teacher training at tertiary level which is to be based on the formed competences of an EFL school teacher and a practitioner of EFL for English major undergraduates.…”
Section: Introductionmentioning
confidence: 67%
“…Expert EFL teachers have more knowledge of learners, learning, and teaching and the ability to combine theoretical and practical knowledge, actively engage students in class and themselves in critical reflection, and respond to different contexts [12,17]. Taken together, the specific features of teachers' professional quality can be divided into two thematic groups: teacher beliefs [24,[35][36][37][38][39][40][41] and teaching capacity [8,10,17,24,[42][43][44][45][46][47].…”
Section: Research On Efl Teachers' Professional Qualitymentioning
confidence: 99%
“…Teacher beliefs were related to their perceptions and thoughts about all aspects of school education, and their attitudes towards teaching and learning over the course of their careers [51,52]. Previous studies have found that teachers display beliefs about language teaching and learning (i.e., an understanding of their own teaching profession and students' learning, as well as the role of the English language) [8,37] and beliefs about language teacher learning and development (i.e., attitudes towards and the pursuit of professional development) [8,36,38,39]. Specifically, beliefs about foreign language teaching and learning have been found to involve teachers' cognition of student-oriented teaching [11,53,54] and their pedagogic goals [8,55].…”
Section: Research On Efl Teachers' Professional Qualitymentioning
confidence: 99%
See 1 more Smart Citation